BTS Speech: A Study of Deictic Usage - Kartikasari, Dika Putri; Maharani , Putu Devi; Hikmaharyanti, Putu Desi Anggerina (Institut Pariwisata dan Bisnis Internasional, 2023)
The title of this research is “BTS Speech: A Study of Deictic Usage in Deictic Expression”. In this research, the writer focuses on how the speaker uses deictic usage pronouns in speech. The speech BTS delivered at the famous UNICEF campaign in February 2018. The speech was about BTS going to tell young people around the world to love themselves with the #LoveYourself campaign. This study aims to identify and classify the types of analyzing the usage of deictic pronouns in BTS Speech. The data studied according to Levinson's (1983) understanding of the theory there are 2 types of deixis, namely: deictic usage and non-deictic usage. Deictic usage is divided into two, namely: Gestural usage and symbolic usage. The most common use of deixis pronouns is symbolic usage. Deixis can be interpreted as a pointer or pointing. The results of the study will show which utterances use deictic usage pronouns. The research will be presented with a qualitative descriptive research method. This research is expected that readers or students can understand the speaker's utterances by paying attention to the use of the pronoun deixis.